A Latin American Music Reader : Views from the South - Simonett, Helena; León, Javier F. (Book collections on Project MUSE., 2016)
This project is a collection of scholarly articles on diverse aspects of Latin American music that have been translated into English from their original issue in Spanish or Portuguese. Each chapter was written by a Latin American author and published between 1986 and 2011. Each has been chosen as representative, outstanding, or influential in some way to the field of Latin American musicology. The intent is to make this significant scholarship available to English-speaking students. The editors have also provided a substantial introduction to survey and contextualize the history of Latin American ethnomusicology.